The law and politics of the Kosovo advisory opinion - Milanović, Marko; Wood, M. C. (Oxford Univ. Press, 2015)
Introduction / Marko Milanović and Michael Wood -- Explaining Serbia's decision to go to the ICJ / James Ker-Lindsay -- Arguing the Kosovo case / Marko Milanoviâc -- The practicalities of representing a client in complex multipart proceedings : the example of Kosovo / Qudsi Rasheed and Michael Wood -- The settling of a self-determination conflict? Kosovo's status process and the 2010 advisory opinion of the ICJ / Bernhard Knoll-Tudor -- Questions of jurisdiction and the discretion to decline a request for an advisory opinion / Vladimir Djeriâc -- The question question / Daniel Mèuller -- Reflections on the ICJ Advisory Opinion on Kosovo : interpreting Security Council Resolution 1233 (1999) / Sean Murphy -- The UN Secretary General and the Advisory Opinion / Mathias Forteau -- The sounds of silence : making sense of the supposed gaps on the Kosovo Opinion / Marc Weller -- The Court and its multiple constituencies : three perspectives on the Kosovo Advisory Opinion / Andrâe Nollkaemper -- The political aftermath of the ICJ's Kosovo opnion / Tatjana Papiâc -- Kosovo -- the questions not asked : self-determination, secession, and recognition / Alain Pellet -- Kosovo and the criteria for statehood in international law / James Crawford -- Has the Advisory Opinion's finding that Kosovo's declaration of independence was not contrary to internationa law set an unfortunate precedent? / Anne Peters -- Some implications of the Advisory Opinion for the resolution of the Serbia-Kosovo conflict / Richard Caplan and Stefan Wolff -- Old problems, fresh frameworks : Kosovo, Serbia and the EU -- the virtue of a 'free territory' / James Gow -- Reflections on the law and politics of the Kosovo case / Harold Hongju Koh